THE ACTIVITY OF ANTIOXIDANTS ENZYMES AND NPK CONTENTS AS AFFECTED BY WATER QAULITY, KINETIN, BIO AND ORGANIC FERTILIZATION IN LETTUCE (Lactuca sativa L.) - & Majid, Altaey (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A  field experiment was conducted using split – split block design to study the effect of irrigation water quality ,organic composts ,kinetin and Bio- health application on N.P.K contents and anti-oxidant enzymes activity  in lettuce, The experiment included three factors ,quality of irrigation water (W) at two levels (1.2, 6.1 dS m-1 ), kind of organic composts Plam fronds and Rice wastes(20)  ton /hectare , kinetin application (50 mg.L-1)  and bio-health fertilizers (5 kg/ hectare). The results indicated that elevation of water salinity levels led to elevation in activity of  Peroxidase POX , Catalase CAT, Malondialdehyde MDA, Superoxide dismutase SOD enzymes and proline contents in leaves, while it decrease leaves contents of ( N.P.K), Organic composts ,  kinetin and bio-health applications alleviated from the negative effects of saline water by increasing  the  (NPK)  contents  in  leaves  ,reduced  POX  ,CAT,  MDA,SOD  and proline , That possible to mitigation the negative affect of salt stress in lettuce the  application of plant growth regulators , bio fertilizers and decomposed organic matter.